PENGARUH REWARD, PUNISHMENT DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA UNIVERSITAS AL-IRSYAD CILACAP - Mispan, Mispan; Jayanti, Esih; Werdiasih, Rustina Dewi (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
This research aims to examine the influence of Reward (X1), Punishment (X2), and Motivation (X3) on Employee Performance (Y) in a study at Al-Irsyad University Cilacap. Data was collected by distributing questionnaires to employees at Al-Irsyad University Cilacap. The sampling technique in this research used convenience sampling, and data was obtained from 96 samples. Data analysis techniques used include validity tests, reliability tests, MSI (Method of Successive Interval) tests, classic assumption tests including linearity tests, normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression analysis, hypothesis tests including t-tests, F-tests and analysis of the coefficient of determination (R²). The results of the study show that reward and punishment do not have a significant effect on employee performance. Meanwhile, motivation has a significant effect on employee performance.